Evaluating the clinical evidence of TCM in Alzheimer’s disease: an evidence map perspective - Cui, Shuqi; Zhao, Yongli; Wang, Xiaowen; Huang, Yingzi; Ye, Jiaxi; Deng, Ziyong; Li, Yanjiang; Qin, Hui; Wang, Li; Li, Yan; Wang, Kaihua; Zheng, Guangshan; et al. (Frontiers in Neurology, 2025)
ObjectiveThis systematic review aimed to synthesize current clinical evidence from randomized controlled trial (RCT) and meta-analyses on the efficacy and safety of TCM in the treatment of Alzheimer’s Disease (AD).MethodsSystematic searches across eight biomedical databases (PubMed, Embase, Web of Science, Cochrane Library, CNKI, Wanfang, VIP, SinoMed) through October 26, 2024 yielded an evidence matrix, which was analyzed through integrated narrative-graphic synthesis.ResultsOur analysis encompassed 187 studies (141 RCTs and 46 systematic reviews/meta-analyses), demonstrating cyclical publication growth with recent contraction. Study characteristics included sample sizes of 50–100 participants and intervention durations of 4–24 weeks. Interventions included acupuncture, herbal decoctions, and proprietary medicines. Outcomes focused on clinical efficacy, scale scores, TCM syndrome scores, and safety. While TCM demonstrated therapeutic potential, prescription heterogeneity and diagnostic ambiguity constrained specificity. Methodological quality was generally low, with few high-quality systematic reviews or meta-analyses.ConclusionWhile TCM shows therapeutic potential in Alzheimer’s disease, methodological limitations persist. Subsequent research requires enhanced trial designs with standardized outcome metrics and rigorous bias control protocols.